KPI’s de performance logística em first mile - Soares, Maria Paula Fernandes Dias (2025)
With the increase in online shopping, the need for faster delivery is becoming increasingly necessary. To achieve this, companies in the logistics sector need to improve delivery at all levels. The objective of this article is to understand how monitoring the quality of the First Mile service (package collection) can be crucial for the product to reach the end consumer faster. The research was conducted by analyzing data provided by a company in the logistics sector through quantitative and qualitative research with an exploratory and empirical approach. As a result, it is observed that monitoring the main indicators can be crucial for mapping the operation, aiming at its improvement and efficiency in collection.